Quest for Freedom A Conversation with Quentin Skinner. - Burton, Howard (Ideas Roadshow Conversations Ser., 2020)
This book is based on an in-depth filmed conversation between Howard Burton and intellectual historian Quentin Skinner, Barber Beaumont Professor of the Humanities at Queen Mary University of London. Quentin Skinner is considered to be one of the founders of the Cambridge School of the history of political thought. This thoughtful, detailed conversation examines how Quentin Skinner came to appreciate the importance of the distinction between the modern view of freedom and the so-called neo-Roman view, together with what it implies for our current and future political understanding.This careful.